Perspectives of Accounting Theory - Rahima Br. Purba; Nurlinda .; Saribulan Tambunan (Universitas Hayam Wuruk Perbanas, 2018)
The importance of strange accounting theory positions is Â used to explain accounting facts accurately and must have logical consistency. Theorists widely use accounting theory in an attempt to explain current phenomena by using robust accounting theories. Accounting theory relies heavily on the agreement on the notion of accounting as a discipline of knowledge. Accounting will be viewed as a science and as a technology. On the basis of the goals to be achieved, accounting theory can be divided into positive and normative theory. By the target of semiotics in communication theory, accounting theory is divided into false, semantic, and pragmatic methods. Accounting theory also derives explanation or justification through deductive and inductive reasoning. Various aspects of accounting theory must be verified or validly tested by logical argument, empirical evidence, predictive power, and agreed value standards.